Hollow-polydopamine-nanocarrier-based near-infrared-light/pH-responsive drug delivery system for diffuse alveolar hemorrhage treatment - Zhang, Lingyan; Li, Mifang; Wang, Yeying; Liu, Yibiao; Zhang, Feiyuan; Lin, Zhihao; Zhang, Yuling; Ma, Mingliang; Wang, Shouju (Frontiers in Chemistry, 2023)
Introduction: Diffuse alveolar hemorrhage (DAH) is a serious complication caused by systemic lupus erythematosus (SLE). Tissue damage and changes in immune response are all associated with excessive free radical production. Therefore, removing excess reactive oxygen species are considered a feasible scheme for diffuse alveolar hemorrhage treatment. Cyclophosphamide is often used as the main therapeutic drug in clinics. However, CTX carries a high risk of dose-increasing toxicity, treatment intolerance, and high recurrence rate. The combination of therapeutic drugs and functional nanocarriers may provide an effective solution. PDA is rich in phenolic groups, which can remove the reactive oxygen species generated in inflammatory reactions, and can serve as excellent free radical scavengers. Methods: We developed a hollow polydopamine (HPDA) nanocarrier loaded with CTX by ionization to prepare the novel nanoplatform, CTX@HPDA, for DAH treatment. The monodisperse silica nanoparticles were acquired by reference to the typical Stober method. PDA was coated on the surface of SiO2 by oxidation self-polymerization method to obtain SiO2@PDA NPs. Then, HPDA NPs were obtained by HF etching. Then HPDA was loaded with CTX by ionization to prepare CTX@HPDA. Then we tested the photothermal effect, animal model therapeutics effect, and biosafety of CTX@HPDA. Results: Material tests showed that the CTX@ HPDA nanoplatform had a uniform diameter and could release CTX in acidic environments. The vitro experiments demonstrated that CTX@HPDA has good photothermal conversion ability and photothermal stability. Animal experiments demonstrated that the CTX@HPDA nanoplatform had good biocompatibility. The nanoplatform can dissociate in acidic SLE environment and trigger CTX release through photothermal conversion. Combining HPDA, which scavenges oxygen free radicals, and CTX, which has immunosuppressive effect, can treat pulmonary hemorrhage in SLE. Micro-CT can be used to continuously analyze DAH severity and lung changes in mice after treatment. The pulmonary exudation in the various treatment groups improved to varying degrees. Discussion: In this study, we report a photothermal/PH-triggered nanocarrier (CTX@HPDA) for the precise treatment of SLE-DAH. CTX@HPDA is a simple and efficient nanocarrier system for DAH therapy. This work provides valuable insights into SLE treatment.